Preparation, Spectral and Thermal Characterization of Two Novel Mixed-Valent and Metal Trinuclear Oxo-centered Complexes - Ghaemi, Arezoo; Tavakkoli, Haman; Khosravi, Iman (Asian Journal of Chemistry, 2012)
Two new oxo-centered trinuclear monochloroacetate complexes, [Mn2Mn(O)(CH2ClCOO)6(py)3] (1) and [Cr2Fe(O)(CH2ClCOO)6 (H2O)3].NO3 (2), were synthesized and characterized by elemental analysis, infrared and electronic spectroscopy and thermogravimetric analysis. These compounds have a typical μ3-oxo trinuclear structure: (a) three metal atoms are situated in the apexes of the equilateral triangle; (b) μ3-oxygen atom and six monochloroacetate ligands fulfill the bridge functions and (c) the monodentate Py or H2O ligands complete the octahedral geometry of the metal ions.